Income Distribution and Consumption Deprivation: An Analytical Link - Mallick, Sushanta K. (Journal of Income Distribution®, 2008)
This article conceives poverty in terms of the consumption of essentialfood, makes use of a new deprivation (or poverty) function, andexamines the effects of changes in the mean and the variance of the incomedistribution on poverty, assuming a log-normal income distribution.The presence of a saturation level of consumption can be treatedas a poverty-line threshold as opposed to an exogenous income-basedpoverty line. Within such a consumption deprivation approach, the articleproves analytically that rising mean income reduces poverty whilerising variance of income distribution increases poverty.